Issues Of Improving Investment Attractiveness in The Development of The Country’s Economy: Problem and Solution - Ochilov Bobur Baxtiyor o‘g‘li (European Science Publishing, 2023)
This article examines the essence of investment attractiveness, the opinions of economists on increasing investment attractiveness in attracting foreign direct investments. Also, the factors influencing the investment attractiveness of our country were analyzed, and internationally recognized indicators assessing the country's business environment and the level of investment risks were discussed. Scientific conclusions and recommendations on increasing investment attractiveness in attracting foreign direct investments have been formulated.
Keywords: investment, investment climate, investment attractiveness, Beri - (Information about business environment risks) index, indicator, foreign direct investment, recipient, donor, business, segment, progression, investment potential.